Pembelajaran Analisis Data dan Peluang Melalui Permainan Bola Voli Berbasis Pendidikan Matematika Realistik Indonesia - Mareta Noor Ahadiya; Siti Mutmainah; Eka Zuliana (LPPM Politeknik Pratama, 2024)
The Indonesian Realistic Mathematics Education Approach (PMRI) is a concept that is suitable for implementation by teachers in elementary schools. This is because PMRI is a mathematical concept that can link activities carried out by students with mathematics learning so that mathematical concepts appear real and can be accepted by students. The purpose of this research is to determine mathematics learning using Indonesian Realistic Mathematics Education through volleyball games, and to find out whether students can use the PMRI approach in solving a problem. The method used in this research is a qualitative descriptive study with the subject being 16 students at SD N 3 Sukosono. Data collection techniques use observation, written tests, and interviews. Research obtained based on the results of student work that has been obtained shows that on average students are able to solve problems using the steps of the PMRI approach. However, there are also some students who are less capable in working on questions using the PMRI approach, such as students' lack of accuracy in entering data. Based on the results, there were 2 students with low ability, 5 students with medium ability, and 9 students with high ability.